Molecular Cloning Studies on Patatin Gene Promoters from Potato Cultivears - Bansal, Saloni (My University, 2007)
Promoters are regarded as molecular biological tools crucial for regulation of gene expression. Tissue-specific or cell type-specific promoters, operate in a particular tissue or cell type and also at certain developmental stages of a plant. These promoters could become very important in terms of driving expression of any gene of interest. Patatin, a major potato tuber protein is encoded by a multigene family. The present study is mainly focussed on molecular cloning and characterization of the 5’ flanking regions of class-I patatin genes from different potato cultivars. Here, four potato cultivars were chosen namely Kufri Chipsona-1 (CS-1), Kufri Chipsona-2 (CS-2), Kufri Chandramukhi (KCM) and Kufri Jyoti (KJ). In order to amplify the 5’ flanking regions of the patatin gene from these cultivars, two different forward primers and one reverse primer was designed based on the class-I patatin gene sequence available in the database (Accession no. X87216). The reverse primer here was used as common. A number of DNA bands got amplified from different cutivars using two sets of primer pairs and then analyzed by agarose gel electrophoresis. Cultivar-wise variation was also noted. The cultivar KJ showed marked variation in terms of the size of the amplified products. The PCR amplified products as obtained using two sets of primers were examined carefully which suggests that the sequences proximal to transcription start site of the gene are relatively conserved and divergence occurs in the farther upstream regions. Only a few DNA bands were chosen for cloning and partial characterization which were as follows: two amplified DNA products (~ 2.2 kb & ~ 2.0 kb) from CS-1 and one (~ 1.4 kb) from KCM corresponding to the first set of primer; similarly one amplified DNA product (~ 0.8 kb) from CS-1 and another (~ 2.0 kb) from KJ DNA corresponding to the second set of primer pair. The selected PCR amplified products were cloned into the SmaI site of pUC19 vector. The putative transformants were selected on the basis of a-complementation (blue/white) for isolation of plasmids. Restriction analyses were carried out to check the presence of cloned inserts. PCR approach was adopted to check first the intactness of the inserts and secondly to see gene specificity. Taken together the results indicate that the cloned inserts correspond to the 5’ flanking region of class-I patatin gene in potato. Further sequencing and functional characterization are required to identify tuber-specific and efficient class-I patatin gene promoters.
Keywords: Molecular Cloning; Patatin Gene; Potato Tubers